2009
DOI: 10.1182/blood-2009-04-219410
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic study on survival of chronic myeloid leukemia and Ph+ acute lymphoblastic leukemia patients with BCR-ABL T315I mutation

Abstract: The BCR-ABL T315I mutation represents a major mechanism of resistance to tyrosine kinase inhibitors (TKIs). The objectives of this retrospective observational study were to estimate overall and progression-free survival for chronic myeloid leukemia in chronic-phase (CP), accelerated-phase (AP), or blasticphase (BP) and Philadelphia chromosome-positive (Ph) ؉ acute lymphoblastic leukemia (ALL) patients with T315I mutation. Medical records of 222 patients from 9 countries were reviewed; data were analyzed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
98
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 114 publications
(105 citation statements)
references
References 21 publications
(28 reference statements)
4
98
1
2
Order By: Relevance
“…CP CML patients with a T315I mutation were extracted from a previously described updated international database containing information from 222 T315I + CML patients (all phases and those with Philadelphia chromosome-positive acute lymphoblastic leukemia). 14 In that study, 14 the survival of T315I + patients did not differ between countries (unpublished data). In this study, the comparison group was CML patients in CP at diagnosis and at IM-resistance, previously screened at IM-resistance for BCR-ABL mutations and found to be T315I negative (they could harbor other mutations).…”
Section: Study Populationmentioning
confidence: 99%
See 3 more Smart Citations
“…CP CML patients with a T315I mutation were extracted from a previously described updated international database containing information from 222 T315I + CML patients (all phases and those with Philadelphia chromosome-positive acute lymphoblastic leukemia). 14 In that study, 14 the survival of T315I + patients did not differ between countries (unpublished data). In this study, the comparison group was CML patients in CP at diagnosis and at IM-resistance, previously screened at IM-resistance for BCR-ABL mutations and found to be T315I negative (they could harbor other mutations).…”
Section: Study Populationmentioning
confidence: 99%
“…14 Mutation screening was performed using different techniques (predominantly direct sequencing, but also polymerase chain reaction-restriction fragment length polymorphisms and denaturing high performance liquid chromatography in combination with sequencing) and, for some patients, included assaying frozen material. Patients with any T315I clone levels were included.…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…16 A recent review of T315I-positive patients has also demonstrated that compared with CML patients in the chronic (CML CP ) or accelerated phase (CML AP ), patients with CML BC and Ph þ ALL have the T315I mutation detected earlier after starting TKI therapy and have lower disease-free and overall survival rates. 17 Aurora kinase inhibitors currently undergoing clinical trial in patients with CML or Ph þ ALL are summarized in Table 1. One of the first reports of the activity of Aurora kinase inhibitors in Ph þ leukemia involved the pan-Aurora kinase inhibitor MK-0457 (previously known as VX-680), which was studied in three adult patients with T315I ABL-mutated CML (n ¼ 2) or Ph þ ALL (n ¼ 1).…”
Section: Ph þ Leukemiasmentioning
confidence: 99%